Changes In Astigmatism Before and After Pterygium Surgery at The Jec Orbita Makassar Eye Clinic From 2021 to 2023 - Hafsah, Waode; Suliati P. Amir; Hanna Aulia Namirah; Sri Irmandha Kusumawardani; Nur Aulia (Jurnal Kedokteran Universitas Palangka Raya, 2025)
Pterygium is an abnormal growth of the conjunctiva onto the cornea that often causes astigmatism and impairs vision. Exposure to ultraviolet (UV) rays is a major risk factor. This study aims to analyze changes in astigmatism in pterygium patients who underwent surgery at the JEC Orbita Eye Clinic in Makassar between 2021 and 2023. An analytical observational study with a cohort approach was used to measure changes in astigmatism before and after surgery. The study sample consisted of 26 patients with pterygium who had complete medical records. Data were collected from medical records and analyzed using the Wilcoxon test. The results showed that the majority of patients (53.8%) had mild astigmatism before surgery. After surgery, most patients (53.8%) still had mild astigmatism, with some patients experiencing a significant decrease. The Wilcoxon test showed a significant difference between astigmatism before and after surgery, indicating a significant improvement in most patients. The conclusion of this study shows that pterygium surgery has a significant effect on reducing astigmatism in patients. Although the majority of patients experienced visual improvement after surgery, some patients still showed high astigmatism. The size of the pterygium and the surgical technique play an important role in postoperative results